A first step towards the resolution of the starvation problem in multi-point-to-point ICRCNs - Fawaz, Wissam (2013)
This letter revolves around an Intermittently Connected Roadside Communication Network (ICRCN) scenario consisting of isolated source Stationary Roadside Units (SRUs) exploiting mobile smart vehicles as store-carry-forward data relays to a destination SRU. In this case, it is observed that a subset of these source SRUs may suffer from a significant starvation problem. In this letter, first, an Markov Decision Process (MDP) framework is established for the purpose of identifying a suitable Bulk Release Decision Policy (BRDP). Second, BRDP is implemented within a Starvation Mitigation and Delay-Minimal (SMDM) bundle delivery scheme. Extensive simulations are conducted for the purpose of: a) quantifying the severity of the starvation experienced by the downstream SRUs and b) gauging the merit of the proposed SMDM scheme through its ability to jointly mitigate starvation and achieve end-to-end delay minimal bundle delivery to the destination SRU.